ICT-based reforms in local government decision-making in the gram panchayats of Kerala (Commonwealth Journal of Local Governance, 2015)
The beneficial impact of computerisation can be felt in all elements that contribute to decision-making in panchayats in the state of Kerala. However, even though computerisation is bringing about immense improvements compared to traditional administrative practices, but scope still remains for further improvement. Instead of the 'as it is' computerisation that is mostly carried out a process based approach is needed.